Implementasi Kebijakan Sistem Zonasi Di Koordinator Wilayah DinasPendidikan Sumbang (Berdasarkan Peraturan Bupati Banyumas Nomor 28Tahun 2021 Tentang Penerimaan Peserta Didik Baru Pada Pendidikan Anak UsiaDini,Sekolah Dasar Dan Sekolah Menengah Pertama Tahun Pelajaran 2021/2022) - Nur’aini Fadhillah; Esti Ningrum; Wahyu Hariadi; Haris Kusumawardana (Wijayakusuma Law Review, 2022)
One of the goals of the Indonesian state is to educate the nation’s life, to the end; the government makespolicies in the field of education, one of which is the school zoning system. However, there still issues withthe implementation process, so the purpose of this research is to determine how the zoning system policyis implemented and the obstacles encountered at the Regional Coordinator of the Sumbang Sub-DistrictEducation Office. A normative/juridical approach method was used in the research to find the law inabstracto in cases in concreto. Secondary data obtained by studying documents is used as the main data,and primary data obtained by conducting interviews is used as supporting data. The qualitative analysismethod is used to conduct the analysis, and deductive reasoning is used to think. Based on the author’sreview of the literature and research, it is possible to conclude that the implementation of zoning systempolicy in the Regional Coordinator of the Sumbang Sub-District Education Office (Based on BanyumasRegent Regulation Number 28 of 2021 concerning Admission of New Students in Early ChildhoodEducation, Elementary Schools, and Junior High Schools for the 2021/2022 Academic Year) has been goingquite well, if not optimaly. The implementation process is hampered by a lack of information and facilities.